The Implication of Flipped Learning Model in Sociology Reading Class - Sholikhi, Fu'ad (Journal of Language, Literature and Teaching, 2023)
This article deals with improving reading skill using the Flipped Learning Model for Sociology students at Islamic University of Balitar. The study was done using classroom action research. Data was collected through a critical reading test, observing students’ participation, and interviews. The study found that students’ critical reading skills were initially low and they lacked the initiative to practice. After using the Flipped Learning Model for two cycles, improvements in their critical reading were observed. The model encouraged twelve Sociology students to participate in learning both in and out of class. The model helped students analyze and evaluate texts, but they still struggled to internalize information and form ideas, as this requires more practice. In the first round of using the Flipped Learning Model, students did better but didn't meet the success target. The highest score was 80 and the mean was 66.56. In the second test, the sociology students did great, with the highest score being 88 and the average score 76.31, which is above the success target. This score shows they really understand and can use what they learned. Within the academic discipline of Sociology, students are frequently tasked with the examination and interpretation of intricate texts and theoretical frameworks. In such a context, the Flipped Learning Model emerges as a particularly advantageous pedagogical approach. It facilitates a self-paced learning environment, enabling students to engage with the material in a manner that aligns with their individual learning rhythms.